The limits to extraction: mining and colonialism in Nunavut. Issue 3 (3rd July 2019) - Bernauer, Warren
ABSTRACT: This article examines the contemporary mining industry in Nunavut, Canada to determine whether land claims and other negotiated agreements have enabled Inuit to capture wealth produced by extraction. It examines the geographic distribution of wealth produced by Nunavut's extractive economy and considers several structural limits to economic development through private-sector extraction in Northern Canada. Although the 1993 Nunavut Agreement has allowed Inuit to increase their share of extraction-based wealth, most wealth still accrues to other jurisdictions. The extractive economy therefore remains a colonial economy, because it continues to benefit external interests disproportionately.